Pengaruh Motivasi, Disiplin Kerja dan Kompensasi Terhadap Kinerja Pegawai Pada Badan Perencanaan Penelitian dan Pengembangan (Baperlitbang) Kabupaten Karimun - Janitra, Muhammad Calvin; Pratama, Bagus Putra (Zona Manajerial: Program Studi Manajemen (S1), 2022)
This study aims to examine and analyze the effect of motivation, work discipline and compensation on employee performance at the Research and Development Planning Agency (Baperlitbang) Karimun Regency. Data was collected through questionnaires distributed to 40 employees at the Research and Development Planning Agency (Baperlitbang) Karimun Regency. The analysis in this study uses the SPSS version 24 program. The data testing technique used is validation test and reliability test with Cronbach Alpha. Classical assumption tests and multiple regression analyses were conducted to test and prove the research hypothesis. The results of the analysis prove that the influence of motivation (X1) has a negative effect on employee performance with a t-count of -0,692 and a insignificant value of 0.493 greater than 0.05. There is a positive and significant effect between work discipline (X2) on employee performance with a t value of 7.784 and a significance value of 0.000, which is smaller than 0.05. There is a positive and insignificant effect on compensation (X3) on employee performance with a t-count value of 0.301 and an insignificant value of 0.765 greater than 0.05. Simultaneously the influence of motivation, work discipline and compensation have a positive and significant effect on employee performance with a calculated F value of 54.625 and a significance value of 0.000 less than 0.05. It can be concluded that motivation has no positive and insignificant effect on employee performance, work discipline has a positive and significant effect on employee performance, and compensation has a positive and insignificant effect on employee performance. Taken together, the effect of motivation, work discipline and compensation has a positive and significant effect on employee performance. From the results of the analysis, it can be seen that employee performance is influenced by the influence of motivation, work discipline and compensation of 0.820 (82,0%), while the remaining 18% is influenced by other factors not examined in this study.